ANALISIS MOTIVASI BELAJAR IPS KELAS VII DI SMP NEGERI 11 KOTA PONTIANAK - Nai Nai; Aminuyati Aminuyati; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to obtain an overview of the level of learning motivation of class VII students of SMPN 11 Kota Pontianak. The instrument of this study was a student motivation motivation questionnaire. The method used in this study was the descriptive method of the purpose of this method to make a systematic description or description of the facts. This study used a qualitative descriptive approach. The sample in this study was class VII students, amounting to 20 students. Questionnaire consists of 20 items that contained 5 indicators, namely: The desire to succeed, there was encouragement and need for learning, there was appreciation in learning, there was a conducive learning environment, there were interesting activities in learning. The data analysis technique used was student learning motivation questionnaire. The results of this study indicated that there are 11 (61.2%) students who have very high learning motivation, 5 (19.5%) students who have high learning motivation and 4 (19.3%) students who have moderate learning motivation. Based on the results of the score per item there was a desire to succeed at 75.00%, the encouragement and learning needs of 80.00%, there was an appreciation in learning at 81.25%, there was a conducive learning environment of 87.50%, the existence of activities interesting in learning was 82.50%. It is known that there was an increase in the results of learning motivation of class VII students of SMP 11 Kota Pontianak. Keywords:Class VII Students,IPS Learning, Motivation